Alienation and its correlation with examination anxiety among a cohort of students at the University of Laghouat - FATTAM, Djallaleddine (Social Sciences Journal)
This study investigates the relationship between test anxiety and alienation among a sample of students at Ammar Tlidji University of Laghouat. It also aims to identify potential differences in the levels of alienation and test anxiety based on variables such as gender, academic major (specialization), and type of residence. The research involved a sample of 70 students (23 males and 47 females) and employed a descriptive correlational methodology. Data collection utilized an alienation measure attributed to "collective Salahuddin," which consists of 80 items across six dimensions, and a test anxiety scale, likely based on Spielberger’s criteria, containing 20 items divided into two dimensions. Statistical analysis included the Pearson correlation coefficient to examine the relationship between test anxiety and alienation, and t-tests to assess the significance of differences based on the demographic variables. The main findings of the study are as follows: There was no significant correlation found between test anxiety and alienation among the participating students at Ammar Tlidji University of Laghouat. No significant differences were observed in the level of alienation among students when analyzed by gender. No significant differences were found in the level of alienation based on the students’ academic major. No significant differences in alienation levels were attributable to the students’ type of residence. Similarly, no significant differences were found in the level of test anxiety among students based on gender. No significant differences in test anxiety levels were observed based on academic major. Finally, no significant differences in test anxiety were found related to the students’ type of residence